KEANEKARAGAMAN JENIS DAN KONDISI EKOSISTEM PADANG LAMUN DI PANTAI MENGIAT, NUSA DUA, BALI - Namira, Alya; Arthana, I Wayan; Kartika, I Wayan Darya (Bumi Lestari, 2021)
This study aimed to determine the diversity, conditions, and diversity of seagrass at Mengiat Beach Bali. The study was conducted for 1 month, January-February 2021. The study was conducted at 3 observation stations using the 50 × 50 cm quadratic transect method. There were 7 types of seagrass, namely Cymodocea rotundata, Syringodium isoetifolium, Halodule pnifolia, Halodule uniinervis, Halophiila ovalis, Thalassodendron cilliatum, and Thalassia hempriichii . The density condition of the seagrass beds at stations I, II, and III was classified as a scale of 5 with the number of stands > 175 ind/m 2 . The species Cymodocea rotundata had the highest density, which was 904 ind/m 2 . The percentage of cover condition at station I in the good criteria of  a rich / healthy condition witha seagrass cover value of 61.73%, while stations II and III were in the damaged category with less rich / unhealthy conditions with value at station II of 58.44. % and station III of 45.97%. There are 10 types of associated biota found namely Tripneustes gratilla, Etisus splendisus, Linckia laevigata, Atergatis floridus, Ophiothrix fragilis, Echinometra viridis, Echinometra mathei, Echinaster luzonicus, and Fromia Milleporella.